Development of parvalbumin-immunoreactive neurons in the postnatal human hippocampal formation - Ábrahám, Hajnalka; Kojima, Hisae; Götzer, Katalin; Molnár, Abigél; Tornóczky, Tamás; Seress, László (Frontiers in Neuroanatomy, 2023)
Introduction: Parvalbumin (PV) is a calcium-binding protein present in fast-spiking GABAergic neurons, such as basket and axo-axonic cells. Previous studies in non-human primates reported prenatal expression of PV in the temporal archicortex including entorhinal cortex and hippocampal formation. In contrast, PV-immunoreactivity was observed only postnatally in the human entorhinal cortex. Regarding PV expression in the human hippocampal formation, no information is available. Methods: In this study, the neurochemical maturation of PV-immunoreactive interneurons was studied in the postnatal developing human hippocampal formation. Results: Before birth, no PV-immunoreactive neurons could be detected in the human hippocampus. At birth, only a few PV-immunoreactive neurons were visible in Ammon’s horn. The first PV-immunoreactive cells in the hilus of the dentate gyrus appeared at the age of 1 month. Even at the age of 5 months, only a few PV-immunopositive cells were present in the dentate hilus. The number of cells and their dendritic and axonal arborization in Ammon’s horn and in the dentate gyrus gradually increased with age. Even at the age of 2 years, dendritic tree and axons of PV-immunoreactive neurons were less complex than can be seen in 8 and 11 years old children. Discussion: Our results showed that long-lasting maturation of PV-immunoreactive interneurons follows the developmental sequence of the subfields of the human hippocampal formation and provides further morphological evidence for the long-lasting functional maturation of the human cortex.